THE PRINCIPAL'S STRATEGY IN DEVELOPING STUDENTS' CHARACTER: (A Case Study at Sma it Assalam Islamic School) - Unzir, Unzir; Yanti, Hera; Iskandar, Iskandar (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
The purpose of this research is to analyze the planning, implementation, supervision, and evaluation carried out by the principal together with stakeholders in developing students' character at SMA IT Assalam Islamic School. This research employs a qualitative method with a descriptive approach. The subjects of the study are the principal and four teachers at SMA IT Assalam Islamic School. Data collection techniques include interviews, documentation, and observation. The conclusion of this study is that the principal of SMA IT Assalam Islamic School has designed and implemented a collaborative strategy for character development, which includes the integration of values such as discipline, honesty, and hard work into the curriculum and extracurricular activities. By involving parents and the school committee, and applying fair disciplinary policies, the principal has successfully established a strong foundation for students’ character formation. Although most students have successfully adopted these values, challenges remain regarding inconsistency among certain students. Systematic supervision and evaluations involving stakeholders demonstrate the success of the program, although continuous improvements are being made to achieve greater consistency and sustainable character development. The findings imply the importance of planning, implementation, supervision, and evaluation that involve all stakeholders for effective character development. Consistency of values between home and school, along with ongoing evaluation, is essential for the program's effectiveness